API generation program: Active immunotherapy CAD106 slows amyloid deposition in cognitively unimpaired APOE4 homozygotes. (31st December 2021) - Riviere, Marie‐Emmanuelle; Turner, Raymond Scott; Sui, Yihan; Laurent, Nathalie; Langbaum, Jessica B.; Cazorla, Pilar; Ricart, Javier; Seneca, Nicholas; Caputo, Angelika; Reiman, Eric M.; Tariot, Pierre N.; Graf, Ana
Abstract: Background: The Alzheimer's Prevention Initiative (API) Generation Study 1 (NCT0256551) evaluated CAD106, an active immunotherapy against Aβ, in delaying the clinical onset of Alzheimer's disease in a cohort of cognitively unimpaired APOE4 homozygotes. Effect of CAD106 on brain amyloid burden after 2 years was measured by amyloid PET. Previous studies in mild AD showed that doses up to 450μg CAD106 induced sustained Aβ‐antibody response with no major safety concerns (Vandenberghe, 2017). Method: Cognitively unimpaired APOE4 homozygotes age 60‐75 were enrolled using a 5:3 randomization ratio (CAD106 450μg:placebo). Intramuscular injections were administered at 0, 6, 12 weeks and then quarterly with alum as adjuvant. PET scans were conducted at baseline and 2 years mainly with florbetapir. Standard uptake value ratios (SUVRs) were calculated using cortical composite region in reference to cerebellum and converted to centiloids. Result: Out of 65 randomized participants (42:23 CAD106:placebo) 59 were followed for 18 months or longer. Mean age at baseline was 65 years, 68% were female. Mean baseline RBANS total score was 106. Year 2 PET scans were acquired in 35 CAD106 and 16 placebo participants with centiloid mean baseline of 49.5 (38.7). CAD106 induced measurable Aβ‐specific IgG titers in all treated participants. Mean (SD) annualized centiloid change from baseline was +8.4 (6.7) on placebo without change with CAD106 ((‐0.9 (5.7), p<0.0001). The effect was more pronounced in amyloid positives: +9.4 (7.7) on placebo and ‐1.8 (6.0) with CAD106, vs in amyloid negatives: +6.7 (4.7) on placebo and +2.2 (2.8) with CAD106. In the CAD106 arm, the effect on PET correlated with antibody titers, especially for amyloid positive subgroup. Higher incidences for psychiatric (21% vs 13%) and general disorders / injection site (64% vs 22%) adverse events were reported with CAD106 vs placebo. Three cases of ARIA (2 ARIA‐H and 1 ARIA‐E) occurred on CAD106 (none on placebo). Cognition scores remained stable for 18 months in both groups. Conclusion: CAD106 is the first active immunotherapy shown to slow amyloid deposition in humans. Treatment with CAD106 might have a positive risk/benefit profile for prevention of amyloid deposition in high‐risk populations.